New species of Endoclita (Lepidoptera: Hepialidae) and revived species status of E. kosemponis from Taiwan - Buchsbaum, Ulf; Grehan, John R. (Zootaxa, 2019)
Two species of Endoclita C. &. R. Felder, 1874 from Taiwan are evaluated for their taxonomic status: Endoclita meifenga Buchsbaum & Grehan sp. n. is described as new for a unique male from the central mountains of Taiwan, and E. kosemponis (Strand, 1916), stat. rev. is elevated to species status. We show that the forewing markings and genitalic characteristics of E. meifenga sp. n. distinguish this species from all other Endoclita. The external appearance of E. kosemponis is similar to E. sinensis (Moore, 1877) but the two species show distinct differences in the male and female genitalia. Preliminary comparison of E. sinensis from Taiwan and Japan suggests they represent more than one species. A sample of the COI gene was sequenced for E. meifenga sp. n. and the primary types of E. meifenga sp. n. and E. kosemponis sp. n. are illustrated here for the first time. The taxonomic status of the non endemic Taiwanese E. davidi (Poujade, 1886) and E. sinensis needs future evaluation.